Alternativas De Solución Para La Afectación Ambiental Por El Uso Del Glifosato En Colombia (2022)
Herbicides are used worldwide to eliminate weeds from crops, one of the best known commercially is glyphosate under the name of Rondoup. During the development of the monograph, issues related to the impacts generated by this chemical on the environment, human health, flora, and fauna are addressed. Its use has increased significantly in recent years due to a series of factors, such as the appearance of resistant seeds that require higher doses and, by reducing the price of the product, production increases. Herbicides are used more frequently due to the capacity of production crops where they must compete for space, nutrients, and other important factors such as water, light, etc. Plants naturally grow alongside crops and can reduce the yield and quality of some crops.